Impeding Bullying Among Young Children in International Group Contexts (Springer International Publishing, 2018)
This volume showcases proven approaches and strategies to diminish the world-wide problem of bullying, and constitutes an overview of an international and multilingual (English, Spanish and Bahasa Indonesian) approach to anti-bullying, harassment, intimidation and teasing (HIBT) education. Chapter topics include the genesis of The Anti-Bullying and Teasing Book in response to a need for program materials for younger children, the tri-lingual implementation of the program in two countries, the infusion of the program into the ongoing curriculum and practice of two schools, the museum as an alternative setting for creative practice, and adaptations of the program based on culture and language. Impeding Bullying Among Young Children in International Group Contexts is a critical resource for educators, administrators, and policy-makers seeking to implement better strategy and policy to combat bullying.